NuSAP4 regulates chromosome segregation in Trypanosoma brucei by promoting bipolar spindle assembly - Qing Zhou; Ziyin Li (Communications Biology)
Abstract Faithful chromosome segregation in eukaryotes requires the assembly of a bipolar spindle and the faithful attachment of kinetochores to spindle microtubules, which are regulated by various spindle-associated proteins (SAPs) that play distinct functions in regulating spindle dynamics and microtubule-kinetochore attachment. The protozoan parasite Trypanosoma brucei employs evolutionarily conserved and kinetoplastid-specific proteins, including some kinetoplastid-specific nucleus- and spindle-associated proteins (NuSAPs), to regulate chromosome segregation. Here, we characterized NuSAP4 and its functional interplay with diverse SAPs in promoting chromosome segregation in T. brucei. NuSAP4 associates with the spindle during mitosis and concentrates at spindle poles where it interacts with SPB1 and MAP103. Knockdown of NuSAP4 impairs chromosome segregation by disrupting bipolar spindle assembly and spindle pole protein localization. These results uncover the mechanistic role of NuSAP4 in regulating chromosome segregation by promoting bipolar spindle assembly, and highlight the unusual features of mitotic regulation by spindle-associated proteins in this early divergent microbial eukaryote.